Review of the modelling approaches for availability contracts in the military context - Rodrigues, Duarte; Erkoyuncu, John Ahmet; Starr, Andrew G.; Wilding, Stephen; Dibble, Alan; Laity, Martin (Elsevier, 2015)
The defence context more recently has been experiencing a significant shift towards servitization. As competition has increased, commercial strategies are increasingly moving towards providing through-life solutions for complex engineering products such as submarines. Within such a context value for money is an essential driver in a life cycle sense for selecting a bid. The defence sector has largely been affected by this change in the business environment. Industrial Product Service System (IPS2) is a model of providing services that satisfy industrial customers and aims to reduce lifecycle impacts of products and services through product servicing, remanufacturing and recycling. This approach has proved to be an effective solution to enhance the services support in military projects. IPS2 offers client value by responding more efficiently to the client demands with reduced prices; it is delivered in the form of contracting approaches between Ministry of Defence (MoD) and industry; these contracts can differ in several aspects as risk sharing, application level, ownership policy and supportability specifications vary. This research focuses on Contracting for Availability (CfA), which is a particular approach of IPS2.The paper aims to present the review of literature in designing support strategies for CfA, identifying the good practices and challenges, and to propose a systematic approach to fill the industrial and academic gap towards an optimization of the current modelling process. This work starts by presenting a literature review in IPS2; it then moves into the optimization processes, describing how contractors currently design a long term service support contract in the military context with better value for money and high level of system readiness. The key cost and performance drivers are identified and a framework is presented to enhance the design process of CfA. The methodology of the paper relies on literature. This research aims to extend the work of several authors in predicting the cost of services in the military contracts.
In: 7th Industrial Product-Service Systems Conference - PSS, Industry Transformation for Sustainability and Business, 21-22 May 2015, Ecole des Mines Saint-Etienne, France
Keywords: IPS2; CfA; Services Support Optimization; Maintenance; Trade-off Analysis; Modelling; Simulation